Neighborhood embedding and re-ranking of disease genes with ADAGIO. - Erden, Mert.; Gelement, Megan.; Hakimjee, Sarrah.; Levin, Kyla.; Sidhom, Mary-Joy.; Devkota, Kapil.; Cowen, Lenore J. (Tufts University. Tisch Library., 2023)
Keywords:; Topic: Applied computing / Life and medical sciences / Computational biology; Topic: Applied computing / Life and medical sciences / Systems biology; Topic: Applied computing / Life and medical sciences / Genetics; Topic: Applied computing; Topic: Applied computing / Life and medical sciences; ACM Open.